Визначення ефективності сучасних методик кінезіологічного тейпування військовослужбовців інституцій сектору безпеки і оборони України в системі спеціальної фізичної підготовки - Ванюк, Дар'я Валеріївна; Некрасов, А. Д.; Газаєв, В. Н.; Лащонов, Ф. Ф.; Грицай, В. В.; Vaniuk, D. V.; Nekrasov, A.; Hazaiev, V.; Lashchonov, F.; Hrytsai, V. (My University, 2023)
В процесі дослідно-аналітичної роботи встановлено, що актуальним питанням впровадження сучасних технік нанесення адгезивної аплікаційної кінезіологічної стрічки на біоланки та окремі частини тіла військовослужбовців інституцій сектору безпеки і оборони України (СБОУ), з метою підвищення ефективності виконання ними завдань за призначенням, присвячено недостатню кількість наукових праць. Це підкреслює актуальність, своєчасність та практичну складову обраного напряму дослідження. Головною метою дослідження є визначення ефективності експериментальної методики кінезіологічного тейпування майбутніх офіцерів інституцій сектору безпеки і оборони України (в системі спеціальної фізичної підготовки) з метою підвищення ефективності виконання ними навчально-бойових та службово-бойових завдань. В результаті емпіричного дослідження членами науково-дослідної групи розроблено, скореговано та апробовано експериментальну методику кінезіологічного тейпування майбутніх офіцерів інституцій СБОУ (в системі спеціальної фізичної підготовки) з метою підвищення ефективності виконання ними навчально-бойових та службово-бойових завдань. In the process of carrying out assigned tasks, servicemen of institutions of the security and defense sector of Ukraine can often suffer injuries, wounds (contusions), which negatively affects the level of combat readiness of units. During the monitoring of scientific-methodical literature, we established that the topical issue of the implementation of effective techniques and methods of kinesiological taping of individual biolinks and body parts of representatives of the security and defense sector of Ukraine, in order to increase the efficiency of their performance of assigned tasks, is devoted to an insufficient amount scientific works. This emphasizes the relevance, timeliness and practical component of the chosen research direction. In the process of research and analytical work, the members of the research group developed, adjusted and tested the experimental technique of kinesiological taping of future officers of the institutions of the security and defense sector of Ukraine (in the system of special physical training) in order to improve the efficiency of their performance of training-combat and service-combat) tasks. The results of the empirical study are implemented in the system of physical training (professional education) of cadets of higher military educational institutions. Prospects for further research in the chosen direction of scientific intelligence include determining the essence and structure of formation of the readiness of commanders of cadet units to organize forms of physical training in the system of professional education of future officers of institutions of the security and defense sector of Ukraine.
Determination of the effectiveness of Modern Methods of Kinesiological taping of Servicemen of Security and Defense Sector Institutions of Ukraine in the System of Special Physical Training
Keywords: апробація; бойова підготовка; витривалість; готовність; кінезіологічне тейпування; майбутні офіцери; методика; педагогічний експеримент; професійні компетентності; професійна освіта; спеціальна фізична підготовка; approbation; combat training; endurance; readiness; kinesiological taping; future officers; methodology; pedagogical experiment; professional competences; professional education, special physical training